Photolytic activation of Ni(II)X2L explains how Ni-mediated cross coupling begins - Max Kudisch; Reagan X. Hooper; Lakshmy K. Valloli; Justin D. Earley; Anna Zieleniewska; Jin Yu; Stephen DiLuzio; Rebecca W. Smaha; Hannah Sayre; Xiaoyi Zhang; Matthew J. Bird; Amy A. Cordones; et al. (Nature Communications)
Abstract Nickel photocatalysis has recently become vital to organic synthesis, but how the Ni(II)X2L pre-catalyst (X = Cl, Br; L = bidentate ligand) becomes activated to Ni(I)XL has remained puzzling and is typically addressed on a case-by-case basis. Here, we reveal a general mechanism where light induces photolysis of the Ni(II)-X bond, either via direct excitation or triplet energy transfer. Photolysis produces Ni(I)XL and a halogen radical, X•. Subsequent hydrogen atom abstraction, often from the solvent, produces a C(sp3) radical, R•, that recombines with Ni(I) to form organonickel(II) complexes, Ni(II)XRL. Rather than acting as a loss pathway, Ni(II)XRL behaves as a light-activated reservoir of Ni(I) via photolysis of the Ni(II)-C bond. These results explain the role of the solvent in protecting the catalyst from off-cycle dimerization, demonstrate that two photons are often required to drive the reaction, and show how tuning the ligand can control the concentration of active Ni(I) species.